A wet-processed, binder-free sulfur cathode integrated with a dual-functional separator for flexible Li–S batteries. Issue 9 (21st February 2020) - Fu, Xuewei; Dunne, Francis; Chen, Min; Zhong, Wei-Hong
Abstract : A dissolving–recrystallizing strategy for fabricating binder-free flexible sulfur cathodes integrated with dual-functional separators is reported. Abstract : Developing flexible, robust and lightweight sulfur cathodes by rationally designing their structures and configurations through a viable and scalable strategy is a critical enabler for fulfilling flexible lithium–sulfur (Li–S) batteries. However, besides the requirements for cathode flexibility, intrinsic limitations from the shuttling of lithium polysulfides and the growth of Li dendrites have restricted the widespread implementations of Li–S batteries. Here, we report a wet-processed strategy by dissolving and recrystallizing S in a suitable solvent to fabricate a flexible, binder-free S cathode. Integrating the resulting S cathode with a dual-functional separator has demonstrated to be able to suppress both the shuttle effect and growth of dendritic Li. The wet-processed strategy not only enables the fabrication of flexible and binder-free S-nanomat cathodes, but also facilitates the deposition of the cathodes on the separators. Meanwhile, a dual-functional separator is fabricated by vapor-phase polymerization of polypyrrole (PPy) coating on both surfaces of the commercial separator, which leads to the reduction of the shuttle effect and the suppression of the growth of dendritic Li simultaneously. As a result, by integrating the S-nanomat and the dual-functional separator, the cathode exhibits exceptional mechanical properties and electrochemical performance. Li–S pouch cells are further demonstrated to show stable cycling performance in the bending state, indicating the feasibility of the integrated S cathode for flexible Li–S batteries.